Substitution Method-Plz help
posted by Svetlana .
Use the Substitution method to solve the system of equations.
x + y = -4
x - y = 2
solve for x in the second equation.
Put that in for x in the first equation:
(y+2) + y = -4
solve for y. Then, x= y+2
i don't get it.How did you get that?What does x equal?
re read my post. I tell you how I got it. you will have then to solve for x, then, put that value of x back in the equation, and solve for y. Post your work.
does x =5?
i have been trying to
figure out how to solve this
problem but i just can't.
it seems so difficult.
i have already seen some
examples but i still don't
SOLVE USING THE SUBSTITUTION METHOD.
please help in the easiest way.
thanks a lot!
teach me how to do this
To solve the system given below using substitution, it is best to start by solving the first equation for y.
11x + y = 12
9y + 3x = 7
can you please explain please :)
Just folow this step and u get ur ansa if u hav a ques lyk x - y =0 eqn1 ,x + y =4.eqn2 . Firs t solv for x . X = 0 + y=y eqn 3 . .then substitute x in eqn 2 . . 0 + y + y =4 . 2y =4. y =2 . . . Sub y in eqn 3 x = y then x=2,y=2